Riding the Waves of Reforms in Corporate Law, an Overview of Recent Improvements in Italian Corporate Codes of Conduct - Fabio Sabatini (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper provides an exploratory analysis on the relationship between educational qualification and work status in Italy, with a particular focus on entrepreneurs and self-employed workers. Rough data are drawn from four waves (1995, 1998, 2002, and 2004) of the Survey of Household Income and Wealth (SHIW) carried out by the Bank of Italy. Stylised facts emerging from the empirical evidence are the surprisingly low level of educational qualification exhibited by employers and the tendency of workers holding higher levels of educational qualification not to choose to undertake an entrepreneurial activity. Such workers generally become members of the arts and professions, or take up a career as high-level employees.
Keywords: I21; J23; J24; M13; 330; Education; Work status; Employment; Self-employment; Entrepreneurship; Human capital; Qualifikation; Akademiker; Erwerbsstatus; Entrepreneurship-Ansatz; Selbstständige; Humankapital; Italien